Traditional health practices for reproductive disorders from Gadchiroli district, Maharashtra, India - P. Y. Bhogaonkar; P. N. Saudagar (Journal of Traditional and Folk Practices (JTFP), 2016)
out during 2010-2012. The survey resulted in documenting health practices pertaining to 61 types of disorders and ailments. Information was collected from 84 local Vaidus. Out of these 9 are disorders and ailments of reproductive system for which about 31 treatments using 31 plant species were found to be in practice. Most of the treatments are for gynecological disorders.